The modern use of hydroxyurea for children with sickle cell anemia - Charles T. Quinn; Russell E. Ware (Haematologica)
Over the past 40 years, the introduction and refinement of hydroxyurea therapy has led to remarkable progress for the care of individuals with sickle cell anemia (SCA). From initial small proof-of-principle studies to multi-center Phase 3 controlled clinical trials and then numerous open-label studies, the consistent benefits of once-daily oral hydroxyurea have been demonstrated across the lifespan. Elevated fetal hemoglobin (HbF) serves as the most important treatment response, as HbF delays sickle hemoglobin polymerization and reduces erythrocyte sickling. Increased amounts of HbF, especially when distributed across the majority of erythrocytes, improve clinical outcomes by reducing hemolytic anemia and preventing vasoocclusion, thereby ameliorating both acute and chronic—and overt and covert—complications. Additional benefits of hydroxyurea beyond HbF induction include lower neutrophil and platelet counts, reduced inflammation, and improved rheology. Toxicities of hydroxyurea in SCA are typically mild and predictable; modest cytopenia is expected and actually therapeutic, while occasional gastrointestinal and cutaneous manifestations are well-tolerated. Long-term risks of hydroxyurea for SCA are mainly theoretical but require ongoing surveillance. Accordingly, hydroxyurea should be initiated as part of standard-of-care, ideally in the first year of life. Proper dosing of hydroxyurea is critical, aiming through stepwise dose escalation to achieve modest but safe myelosuppression, with periodic adjustments for weight gain. Precision dosing using pharmacokinetics may facilitate optimal dosing without frequent dose adjustments. Although transformative and even curative therapies for SCA are emerging, hydroxyurea is the only available and accessible disease-modifying treatment that can address the global burden of disease, especially in low-resource settings within sub-Saharan Africa.